Assessment of the occupational eye lens dose for clinical staff in interventional radiology, cardiology and neuroradiology. (24th January 2017) - Omar, Artur; Kadesjö, Nils; Palmgren, Charlotta; Marteinsdottir, Maria; Segerdahl, Tony; Fransson, Annette
Abstract: In accordance with recommendations by the International Commission on Radiological Protection, the current European Basic Safety Standards has adopted a reduced occupational eye lens dose limit of 20 mSv yr –1 . The radiation safety implications of this dose limit is of concern for clinical staff that work with relatively high dose x-ray angiography and interventional radiology. Presented in this work is a thorough assessment of the occupational eye lens dose based on clinical measurements with active personal dosimeters worn by staff during various types of procedures in interventional radiology, cardiology and neuroradiology. Results are presented in terms of the estimated equivalent eye lens dose for various medical professions. In order to compare the risk of exceeding the regulatory annual eye lens dose limit for the widely different clinical situations investigated in this work, the different medical professions were separated into categories based on their distinct work pattern: staff that work (a) regularly beside the patient, (b) in proximity to the patient and (c) typically at a distance from the patient. The results demonstrate that the risk of exceeding the annual eye lens dose limit is of concern for staff category (a), i.e. mainly the primary radiologist/cardiologist. However, the results also demonstrate that the risk can be greatly mitigated if radiation protection shields are used in the clinical routine. The results presented in this work cover a wide range of clinical situations, and can be used as a first indication of the risk of exceeding the annual eye lens dose limit for staff at other medical centres.